Students' Perspectives on Learning Practical Nursing Skills: A Focus Group Study in Norway - A. G. Gregersen; M. T. Hansen; S. E. A. Brynhildsen; V. A. Grøndahl; A. C. Leonardsen (Hindawi Limited, 2021)
Practical nursing skills are complex and involve technical, theoretical, and practical aspects, caring perspectives adjusted to both patient and circumstances, as well as ethical and moral considerations. Patients' length of stay in hospitals is decreasing, and more advanced patient treatment is conducted in primary healthcare settings. Hence, education and nursing skills need adjustment in line with the rapidly evolving field of practice. Studies emphasize a need to uncover whether the technical aspect of nursing skills, in general, is challenging in students' learning. The aim of this study was to explore students' perspectives on practical nursing skills and how they can best learn these. Three focus group interviews were conducted with registered nurse students and intellectual disability nurse students in their last semester (n = 11). Conventional, inductive content analysis in line with recommendations from Hsieh and Shannon was used to analyze the data. Two main categories with subcategories were identified: (1) the content of practical skills, with subcategories (a) human-to-human relations, (b) organizational competence, and (c) technical mastering and (2) building competence, with subcategories (a) need for supervision, (b) planning the learning situations, and (c) relevance for practice. Students experienced that practical skills did not only include technical aspects but also the ability to establish a relationship to the patient and to organize their working day. Supervising was assumed as essential both when training in the simulation center and in clinical placement, as well as planning of the training, respectively. Students experienced that some skills learned in the university college were less relevant in clinical practice and that certain skills were difficult to perform in practice due to the type of clinical placement. Hence, there is a need to review the approach to and content of practical nursing skills' learning in healthcare undergraduate programs, to prepare students for clinical practice, and to ensure that they build the competence needed in healthcare services.